Fenomena Kelautan dalam Al-Qur'an Menurut Agus S. Djamil: Studi tentang Batas Dua Laut, Kegelapan Laut, dan Sungai Bawah laut - Dea Destiani; Regina Cahyani Putri; Vera Nungki; Siti Nuraisyah; Andi Rosa (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This article examines three marine phenomena mentioned in the Qur'an based on the perspective of Agus S. Djamil as presented in his book Batas Dua Laut: Al-Quran Menyibak Rahasia Lautan (The Boundary Between Two Seas: The Qur'an Unveils the Secrets of the Ocean) (2012). The three phenomena discussed are the barrier between two seas (barzakh), the layers of darkness in the deep sea, and the existence of underwater rivers. This research employs a descriptive qualitative method with a library research approach to analyze the writing structure, interpretive method, and substance of Djamil's interpretation, as well as to compare them with the latest findings in oceanography and marine geology. The findings show that Djamil systematically organizes his book using an approach that combines popular and academic elements, moving from simpler to more complex phenomena, while inserting theological and economic connections in each section. The interpretive method used is a parallelist approach, which emphasizes the use of measurable empirical data as the basis for reading kauniyah (cosmic) verses, while avoiding potentially unstable theories. The substance of the interpretation introduces three progressive innovations. First, the concept of the barrier between two seas is examined not only vertically but also horizontally, creating a broader understanding of the gift of lu’lu wal marjan (pearls and coral). Second, the interpretation of QS An-Nur [24]: 40 regarding the darkness of the deep sea is reinforced with contemporary oceanographic data on thermoclines, significant light intensity reduction at depths exceeding 200 meters, and the presence of internal waves. Third, the phenomenon of underwater rivers is explained through the discovery of submarine canyons and submarine fans, which have only been identified thanks to modern technology. These three interpretations bring a new value in the form of istikhraj al-‘ilmi (scientific derivation) that is not merely theoretical but also applicative, and they make a significant contribution to the development of scientific exegesis (tafsir ilmi) in Indonesia.